Implementasi Asesmen Autentik dalam Kurikulum Merdeka: Studi Fenomenologi pada Guru Penggerak di Sekolah Dasar - Armiya Nur Lailatul Izzah (https://journal.metanusantara.com/pedagogia, 2025)
The Merdeka Curriculum positions authentic assessment as a key component in assessing students' holistic development. However, its implementation at the elementary school level faces various complex challenges. This qualitative phenomenological study aims to explore the experiences of Driving Teachers in implementing authentic assessment. Research data were collected through in-depth interviews with 10 Driving Teachers in elementary schools who have implemented the Merdeka Curriculum for at least one year. The research findings reveal three main themes. First, there is a transformation of mindset from conventional assessment paradigms towards a facilitative-reflective approach. Second, teachers face dynamic challenges including administrative burdens and time constraints, yet develop collaborative strategies through communities of practice and technology utilization. Third, the implementation of authentic assessment significantly enhances student engagement and teachers' holistic understanding of student development. This study concludes that the implementation of authentic assessment is a transformative process requiring systemic and collaborative support. The development of digital platforms to simplify documentation and strengthen sustainable communities of practice is recommended.